Reliability of a standing isokinetic shoulder rotators strength test using a functional electromechanical dynamometer: effects of velocity - Martinez-Garcia, D.; Rodriguez-Perea, A.; Barboza, P.; Ulloa-Diaz, D.; Jerez-Mayorga, D.; Chirosa, I.; Chirosa Rios, L. J. (PeerJ, 2020)
Background: The evaluation of the force in internal rotation (IR) and external rotation (ER) of the shoulder is commonly used to diagnose possible pathologies or disorders in the glenohumeral joint and to assess patient`s status and progression over time. Currently, there is new technology of multiple joint isokinetic dynamometry that allows to evaluate the strength in the human being. The main purpose of this study was to determine the absolute and relative reliability of concentric and eccentric internal and external shoulder rotators with a functional electromechanical dynamometer (FEMD).